2014
DOI: 10.3748/wjg.v20.i25.8092
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic studies of human gastric cancer: Review

Abstract: Metabolomics is a field of study in systems biology that involves the identification and quantification of metabolites present in a biological system. Analyzing metabolic differences between unperturbed and perturbed networks, such as cancerous and non-cancerous samples, can provide insight into underlying disease pathology, disease prognosis and diagnosis. Despite the large number of review articles concerning metabolomics and its application in cancer research, biomarker and drug discovery, these reviews do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 0 publications
0
48
0
1
Order By: Relevance
“…Given the importance of metabolic cues in the regulation of inflammatory responses both in macrophages as well as T-cells, metabolomics has been used to study such perturbations in numerous diseases (Jayavelu and Bar 2014; Wen et al, 2013; Barallobre-Barreiro et al 2013; Wang et al 2010; DeFeo et al 2011; Lu et al 2013; Noga et al 2012). However, the role of metabolomics in sarcoidosis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of metabolic cues in the regulation of inflammatory responses both in macrophages as well as T-cells, metabolomics has been used to study such perturbations in numerous diseases (Jayavelu and Bar 2014; Wen et al, 2013; Barallobre-Barreiro et al 2013; Wang et al 2010; DeFeo et al 2011; Lu et al 2013; Noga et al 2012). However, the role of metabolomics in sarcoidosis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The development of metabolome analysis tools is allowing the application of comprehensive analyses of energy metabolism pathways such as glycolysis, pentose phosphate pathway (PPP), tricarboxylic acid (TCA) cycle, urea cycle, amino acid and nucleotide metabolisms, and GSH metabolism in cells and tissues. Several articles have been published on metabolomic applications in gastric cancer (27,34,35). However, none have focused on associations between energy metabolism and CD44v9 expression.…”
mentioning
confidence: 99%
“…[ ] The mainly pathological features of CAG involved atrophy of gastric mucosa, decrease of gastric acid secretion, activation of gastric parietal cells and intrinsic factors, lack of serum autoantibodies, hypochlorite and vitamin B12, and neurological symptoms and diffuse metaplasia. [ ] In some cases, CAG showed significant spasmolytic polypeptide expressing metaplasia (SPEM) and intestinal metaplasia.2 [ ] Previous studies have shown that the mechanism of CAG is due to oxidative stress, inflammation, and endothelial and mucosal dysfunction. [ ] However, its accurate mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%